Define $g:\mathbb{R^2} \rightarrow \mathbb{R^2}$ by $(x,y)=g(s,t)=(st,e^t)$ and let $\omega= xdy$. How can I compute $d\omega$ and $g^\ast \omega$?

Actually, I computed $d\omega =tds \wedge e^tdt$. (Is this true?) However I am confused about the pullback map.

  • 1
    $\begingroup$ Your $d\omega$ cannot be correct: differentiating a 1-form you get a 2-form but $t ds + e^t dt$ is a 1-form. $\endgroup$ – Giuseppe Negro Dec 30 '11 at 15:41
  • $\begingroup$ @GiuseppeNegro You're right. There's a typo, it should be $tds \wedge e^tdt$. I've corrected it. $\endgroup$ – user20353 Dec 30 '11 at 15:47

Let's deal with $\mathrm{d} \omega$ first. The exterior derivative of a differential form is defined purely in terms of that differential form, so $g$ never enters the picture here. The Leibniz rule for exterior derivatives is $$\mathrm{d} (\alpha \wedge \beta) = \mathrm{d} \alpha \wedge \beta + (-1)^p \alpha \wedge \mathrm{d} \beta$$ where $\alpha$ is a $p$-form. Hence, $$\mathrm{d} (x \, \mathrm{d} y) = \mathrm{d} x \wedge \mathrm{d} y - x \, \mathrm{d}^2 y = \mathrm{d} x \wedge \mathrm{d} y$$ since $\mathrm{d}^2 y = 0$.

The pullback of a differential form by a smooth map is a little more confusing. Recall that a $1$-form $\alpha$ on a manifold $M$ is a smooth map $\alpha : M \to T^* M$ such that $$\alpha |_p \in T^*_p M \text{ for each } p \text{ in } M$$ where I have written $\alpha |_p$ to mean the value of $\alpha$ at $p$. But an element of $T^*_p M$ is a linear map $T_p M \to \mathbb{R}$, so given a smooth map of manifolds $g : M' \to M$, at each point $p'$ of $M'$, we have $$\alpha |_{g(p')} \circ \mathrm{D}g |_{p'} : T_{p'} M' \to \mathbb{R}$$ where $\mathrm{D}g |_{p'} : T_{p'} M' \to T_{g(p')} M$ is the Jacobian of $g$ at $p'$. Thus this yields a $1$-form on $M'$ $$g^* \alpha : M' \to T^* M'$$ defined by $$g^* \alpha |_{p'} = \alpha |_{g(p')} \circ \mathrm{D}g |_{p'}$$

Now, this only looks complicated, but it really isn't. Since $g(s, t) = (x, y) = (st, \exp t)$, we have $$\begin{align} g^* \mathrm{d} x & = t \, \mathrm{d} s + s \, \mathrm{d} t \\ g^* \mathrm{d} y & = \exp(t) \, \mathrm{d} t \end{align}$$ and $g^*$ is a homomorphism of exterior differential algebras, so $$g^* (x \, \mathrm{d} y) = s t \exp(t) \, \mathrm{d} t$$ which is exactly what you would expect from naïvely pushing around differential operators and substituting! (This is partly the reason why some people simply omit the notation $g^*$.)


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.